1988
DOI: 10.1071/sr9880217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbial C, N-flush and ATP, and certain enzyme activities of different textured soils subject to gradual drying

Abstract: A clay loam, a silt loam and a sand soil were gradually dried from field moisture content to air-dryness at 25�C in the laboratory. Microbial C measured by substrate-induced respiration (SIR), fumigation-incubation (FI) and fumigation-extraction (FE), microbial N-flush measured by FI and FE, microbial ATP content, and soil phosphatase and sulfatase activities were monitored throughout a drying period of approx. 60 h achieved over 16 days. All the microbial and enzyme variables declined as the gravimetric soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 0 publications
0
17
1
2
Order By: Relevance
“…Van Veen et al (1984) argued that the composition of clay in soil influenc exits microbial preservation capacity. Similarly, West et al (1988) also found that clay loam soil had maximum levels of microbial C and N-flush compared to the sandy soils.…”
Section: Influence Of Microsites and Seed Viability On Re-developmentmentioning
confidence: 84%
“…Van Veen et al (1984) argued that the composition of clay in soil influenc exits microbial preservation capacity. Similarly, West et al (1988) also found that clay loam soil had maximum levels of microbial C and N-flush compared to the sandy soils.…”
Section: Influence Of Microsites and Seed Viability On Re-developmentmentioning
confidence: 84%
“…Under laboratory conditions, air-drying can markedly lower microbial C and N values, particularly in a sandy soil (West et al, 1988). In our environmental rooms, plant growth continued, although to a much reduced extent, during the slow 'summer' drying.…”
Section: Properties Of the 'Summer'-dried Soilmentioning
confidence: 95%
“…Number of soil types and type of land use Clay (%) SOC (g kg À1 ) Experimental conditions: Duration of air drying method used to determine microbial biomass Changes in microbial biomass C due to air drying: field moist vs. air dried samples Sparling et al, 1986 16; pasture Not given 17e88 10 days Chloroform fumigationeincubation method (Jenkinson and Powlson, 1976; K c factor: 0.45) Substrate-induced respiration technique (Anderson and Domsch, 1978;West and Sparling, 1986) 1e75% decrease (12 soils) 4e98% increase (4 soils) 3e69% decrease West et al, 1988aWest et al, , 1988b 6; pasture 4e55 53e91 16e17 days Chloroform fumigationeincubation method (Jenkinson and Powlson, 1976; K c factor: 0.45) Substrate-induced respiration technique (Anderson and Domsch, 1978;West and Sparling, 1986) Fumigationeextraction moist soil samples. These authors used the carbohydrate signatures of the released hydrophilic substances to demonstrate a strong contribution of microbial derived compounds to WEOM.…”
Section: Studymentioning
confidence: 99%